Workforce Diversity and It’S Benefits In Organizations: Understanding the Importance and Challenges of Workforce Diversity in Organizations (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Workforce diversityis a primary concern for most of the businesses. Today’s organisations need torecognise and manage workforce diversity effectively. Many articles have been written on this topic butthere is no specific definition of workforcediversity.Themainpurpose of this article isto review theliterature of workforcediversity. What isworkforce diversity? What are the benefitsof workforcediversity in organisations, what management can do to enhance work force diversityin organisations? What are the disadvantagesof workforce diversity? .This questions would bemainpurpose of this article.